Development of Moodle Application on the Subject of Fungi as a Biological Learning Resource for High School Students - Erika Arifiana; Imam Mudakir; Mochammad Iqbal (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2018)
This study aimed to develop a web-based learning materials using Moodle Application. This was a Research and Development study. The data were collected using needs analysis questionnaire, pre-test/post-test, student responses questionnaire, and experts validation. The development process was carried out using ADDIE model (Analyze, Development, Design, Implemantation, Evaluation). The result showed that all expert judgments were on satisfaction category. The content expert gave 80,23%, the learning media expert gave 80,7%, while the development expert agree in the point of 75% and teacher as user prospectus gave agreement on 80%. Keywords: Teaching Materials, Moodle application, ADDIE